The Relevancy Of Just-In-Time (JIT) Concept In Government Purchasing - Chai, Khin Chung; Abu Bakar, Nooh (Penerbit UTM/UTM Press, 2001)
Just-in-Time (JIT) concept has been applied with considerable success in manufacturing environment. This paper provides insights of JIT concept and the pre-requisites for successful application of JIT in either private or public sectors. Although JIT concept has many advantages, a current study suggested that its application couldn't be applied in total to Government purchasing environment. Nevertheless, the essence of JIT concept in the context of supply management can and should be exploited.